Comparisons of Science Motivational Beliefs of Adolescents in Taiwan, Australia, and the United States: Assessing the Measurement Invariance Across Countries and Genders - Liou, Pey-Yan; Lin, John J. H. (Frontiers in Psychology, 2021)
This study utilized international, large-scale assessment data to compare adolescents’ science motivational beliefs within and between countries and genders. The study focused on eighth graders’ beliefs about science, including their science self-concept, the intrinsic value they ascribed to science, and their beliefs about the subject’s utility. The study data derived from the 2019 Trends in International Mathematics and Science Study (TIMSS) conducted in Taiwan, Australia, and the United States. To ensure the validity of mean cross-group comparisons, the measurement invariance (MI) of the constructs was first assessed. Multiple-group confirmatory factor analysis and latent factor mean comparisons were applied to the data. The results indicated that the MI of science motivational beliefs across the three countries attained only metric invariance, rendering a latent mean comparison implausible. However, the cross-gender MI within each country attained scalar invariance, supporting the comparison of means across genders. The science motivational beliefs of females were significantly lower than those of males, with the exception of U.S. students’ beliefs about its utility value. The findings of this study raise concerns about the validity of current international comparisons of students’ science motivational beliefs while supporting the use of TIMSS data to identify gender differences in science motivation within each country. The implications of MI across countries and genders are discussed, and the importance of establishing MI is highlighted. The findings affirm that gender disparities in science motivational beliefs can be compared using constructs with sound psychometric properties.